(untitled) (The University of Nairobi Journal of Language and Linguistics, 2026)
This paper explores the pragmatic factors that influence word order in the Nandi language, in which word order plays an important role in encoding pragmatic functions such as focus, topicalization, contrast, and emphasis. Although the syntactic structure of Nandi has been previously described, little attention has been given to how word-order choices are influenced by pragmatic considerations. This study addresses this gap by investigating how word order in Nandi is influenced by pragmatic factors. The study applies Role and Reference Grammar (RRG) as a theoretical framework to examine how pragmatic factors such as focus and topic drive variations in simple clause constructions. The findings reveal that Verb Subject Object (VSO) is the dominant word order, and that the Verb Object Subject (VOS) word order and other word orders, such as Subject Object Verb (SOV), Subject Verb Object (SVO), and Object Verb Subject (OVS), are used systematically in particular pragmatic environments. The study contributes to both the descriptive understanding of Nandi syntax and the theoretical modelling of word order flexibility in VSO languages, as well as providing comparative insights for the Nilotic language family.